2018
DOI: 10.1021/acs.jafc.8b04956
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Root Physiological and Proteomic Responses to Dibutyl Phthalate Exposure between Low- and High-DBP-Accumulation Cultivars of Brassica parachinensis

Abstract: Di-n-butyl phthalate (DBP), as an endocrine-disrupting chemical that tends to be accumulated in crops, poses great risks to human health through the food chain. To identify the molecular mechanism underlying differences in their DBP accumulation, the root physiological and proteomic responses to DBP stress of two Brassica parachinensis cultivars, a high-DBP accumulator (Huaguan) and a low-DBP accumulator (Lvbao), were investigated. Root damage of greater severity and significantly greater (p < 0.05) decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Two parallel samples were prepared, one was cut with sterilized scissors and quickly frozen in liquid nitrogen for RNA sequencing (RNAseq) and the other was naturally dried for metabolite determination. The remaining plants were collected and deposited as voucher specimens (Zhao et al, 2018;.…”
Section: Plant Materials and Salinity Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two parallel samples were prepared, one was cut with sterilized scissors and quickly frozen in liquid nitrogen for RNA sequencing (RNAseq) and the other was naturally dried for metabolite determination. The remaining plants were collected and deposited as voucher specimens (Zhao et al, 2018;.…”
Section: Plant Materials and Salinity Treatmentsmentioning
confidence: 99%
“…Ions with the same m/z value in different samples were set at a maximum tolerance of 10 ppm and the same retention time (tR) was set at a tolerance of 0.2 min (Wang et al, 2019). Compounds were quantified based on means of the relative peak area and all analyses were conducted in triplicates (Rizzato et al, 2017;Zhao et al, 2018).…”
Section: Metabolite Profiling Analysis Of Bioactive Constituents In Licoricementioning
confidence: 99%
“…Plasticisers are an important type of chemical additive which improve the plasticity of a polymer so are widely applied in plastics for cosmetics and food packaging material (Frederiksen et al, 2007;Schecter et al, 2013;Wittassek et al, 2011;Zhang et al, 2013). However, they are considered as the fourth most toxic chemical substance, and as they are only physically combined with plastic and other materials, they can be easily dissolved by oil and other substances to enter the human body through the respiratory and digestive tracts and the skin (Bi et al, 2013;Lu et al, 2019;Zhao et al, 2018). Recent studies have found that phthalates have been detected in the blood of girls, the urine of women of childbearing age (Wang et al, 2015;Watkins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…compared to OP LACVs. 46,49 The mechanism responsible for DBP LACVs of Chinese flowering cabbage (Lvbao) was studied with quantitative proteomics. 48,49 More than 150 differentially expressed proteins were detected in the DBP LACVs (Lvbao) when compared to the crops with high accumulation (Huaguan).…”
Section: ■ Introductionmentioning
confidence: 99%
“…46,49 The mechanism responsible for DBP LACVs of Chinese flowering cabbage (Lvbao) was studied with quantitative proteomics. 48,49 More than 150 differentially expressed proteins were detected in the DBP LACVs (Lvbao) when compared to the crops with high accumulation (Huaguan). 48,49 DBP LACVs have the downregulated differentially expressed proteins associated with cell wall synthesis, energy metabolism, antioxidation activity, and signal transduction, which show a lower tolerance to DBP and a corresponding limited DBP accumulation.…”
Section: ■ Introductionmentioning
confidence: 99%